Identification of Calcium and Phosphate Content in Chicken Bones and Duck Bones (Future Science)
The production of poultry such as chickens and ducks, especially in East Java, is very large, so the bone waste produced is of course the same. Generally, minerals in bone are dominated by calcium, phosphorus and magnesium. Phosphate is a derivative of phosphorus. Phosphate is an anion consisting of phosphorus (P) and oxygen (O) atoms. Calcium and phosphate are as important as sodium and potassium in the regulation of basic body functions. The purpose of this study was to determine the identification of calcium and phosphate in chicken bone and duck bone waste. Beginning with cleaning and then proceeding with drying on each of the chicken bone and duck bone waste using an oven for 1 hour at a temperature of 110ºC. Then the dried bone was ground until it reached 30 mesh and then weighed until it reached a weight of 50 grams. Furthermore, tests were carried out using AAS and gravimetry to determine the content of calcium and phosphate in chicken and duck bones. On chicken bones for the gravimetric test method obtained phosphate content of 6.7% and with the AAS test method obtained a calcium content of 24.9%. In duck bone with gravimetric test method for phosphate content obtained by 7.35% and with AAS test method obtained calcium content of 30.82%.